The Need To Change Return to Play Testing in Athletes Following ACL Injury: A Theoretical Model - Kevin E Wilk; Zachary M Thomas; Christopher A Arrigo; George J Davies (North American Sports Medicine Institute, 2023)
The incidence of knee injuries in sport, particularly involving the ACL, appears to be increasing yearly, especially in younger age athletes. Even more concerning is the frequency of ACL reinjury also appears to be increasing year after year. Improving the objective criteria and testing methods used to determine return to play (RTP) readiness following ACL surgery is one aspect of the rehabilitation process that can significantly help in reducing reinjury rates. Currently, the majority of clinicians are still using post operative time frames as their number one criterion for clearance to RTP. This flawed method demonstrates an inadequate reflection of the true unpredictable, dynamic environment athletes are returning to participate in. In our clinical experience, objective testing to allow for clearance to sport participation following an ACL injury should incorporate neurocognitive and reactive testing due to the nature of the injury typically occurs because of failed control of unanticipated reactive movements. The purpose of this manuscript is to share a neurocognitive testing sequence we currently employ consisting of 8 tests in 3 categories: Blazepod tests, reactive shuttle run tests, and reactive hop tests. The use of a more dynamic reactive testing battery may decrease the reinjury rates when an athlete is cleared for participation by measuring readiness in chaotic circumstances that are more truly reflective of the sporting environment the athlete is working to return to and in the process give them a greater sense of confidence.